OBJECTIVE NECESSITY AND IMPORTANCE OF THE DEVELOPMENT OF TERRITORIAL TOURISM IN THE CONDITIONS OF THE FORMATION OF THE DIGITAL ECONOMY - Dustmurodov Orifjon Ismatilloevich (Journals Park Publishing, 2022)
This article provides information on the introduction of new types of services to recreational areas in the context of the formation of the digital economy, development of Rakham services, increasing economic efficiency, further development of tourism services in the sustainable development of the economy, attracting direct investment in the development of tourism services to the regions, creating new jobs as well, Feedback and feedback on the development of services" HR", the scientific and methodological approach to the regulation of the tourism services market are presented.
Keywords: digital economy, recreational areas, tourist resource, objective necessity, digital services, economic efficiency, currency exchange, direct investment.